Dead water : a Shetland mystery - Cleeves, Ann (Cleeves, Ann. Shetland series, 2014)
"Ann Cleeves returns to her critically acclaimed Shetland Island series with this stunning mystery featuring Inspector Jimmy Perez, who readers will remember from Raven Black, White Nights, Red Bones, and Blue Lightning. When the body of a journalist is found, Detective Inspector Willow Reeves is drafted from outside to head up the investigation. Inspector Jimmy Perez has been out of the loop, but his local knowledge is needed in this case, and he decides to help Willow. The dead journalist had left the islands years before to pursue his writing career. In his wake, he left a scandal involving a young girl. When Willow and Jimmy dig deeper, they realize that the journalist was chasing a story that many Shetlanders didn't want to come to the surface. In Dead Water, a triumphant continuation to her Shetland series, Ann Cleeves cements her place as one of Britain's most successful crime writers. "--